Petri net‐based deviation detection between a process model with loop semantics and event logs. (17th January 2018) - Wang, Lu; Du, YuYue; Qi, Man; Qi, HongDa; He, ZhaoYang
Summary: Information systems have been widely used to realize business processes. The business processes can be described by formal or semi‐formal models. In practice, there are a number of realistic processes involving loop semantics. As an insufficient design or improvement of the information system, event logs generated from these systems may not be consistent with the existing models. By comparing an existing process model with the event logs, we can detect inconsistencies called deviations and verify and extend the business process model. In this paper, some abnormal activities in business processes are formally defined based on Petri nets. An efficient approach to detect deviations between the process model with loop structures and event logs is proposed. A clinical process in a healthcare information system is used as a case study to illustrate our work. Experimental results show the effectiveness and efficiency of the presented approach.